Household opportunity costs of protecting and developing forest lands in Son La and Hoa Binh Provinces, Vietnam - Lan, Le Ngoc; Wichelns, Dennis; Milan, Florence M.; Hoanh, Chu Thai; Duy Phuong, Nguyen (Uopen Journals, 2016)
Vietnam has pilot-tested a payment for forest environmental services (PFES) program in an effort to restore and protect forest areas, some of which have been severely degraded by the excessive cutting of trees by small-scale farmers planting annual crops on steep, sloping lands. The pilot program implemented in southern Vietnam seems to be successful, yet the program in northern Vietnam has not produced the desired rates of planting and maintaining forest areas. The reasons for these mixed results include differences in socio-economic characteristics and also the production and marketing opportunities available to rural households in the project areas. To gain insight regarding program participation, we examine the household-level opportunity costs of planting and -maintaining small plots of forest trees in northern Vietnam. We find that small-scale farmers in Hoa Binh Province, with limited financial resources, prefer the annual revenue stream provided by crops such as maize and cassava, rather than waiting for 7 years to obtain revenue from a forest planting. Farmers in Son La Province, with limited access to markets, prefer annual crops because they are not able to sell bamboo shoots and other forest products harvested from their small plots. In both provinces, the payments offered for planting and maintaining forest trees are smaller than the opportunity costs of planting and harvesting annual crops. Thus, most households likely would choose not to participate in the PFES program, at current payment rates, if given the opportunity to decline.